Effect of Modulating Activity of DLPFC and Gender on Search Behavior: A tDCS Experiment - Yang, Xiaolan; Lin, Yiyang; Gao, Mei; Jin, Xuejun (Frontiers in Human Neuroscience, 2018)
Studies of search behavior have shown that individuals stop searching earlier and accept a lower point than predicted by the optimal, risk-neutral stopping rule. This behavior may be related to individual risk preference. Studies have also found correlativity between risk preference and the dorsolateral prefrontal cortex (DLPFC). As risk attitude plays a crucial role in search behavior, we studied whether modulating the activity of DLPFC, by using the transcranial direct current stimulation (tDCS) device, can change individual search behavior. We performed a sequential search task in which subjects decided when to accept a point randomly drawn from a uniform distribution. The results showed that the subjects receiving right anodal/left cathodal stimulation stopped searching late, significantly increased their accepted point, which was greater than predicted by the optimal rule, and generated a significantly higher search income. That is, those subjects may have changed their risk attitude to search for a higher acceptable point and receive a higher benefit. Besides, the effect of stimulation on search behavior was mainly driven by the female subjects rather than by the male subjects.